Atomic structures of Coxsackievirus A6 and its complex with a neutralizing antibody - Longfa Xu; Qingbing Zheng; Shaowei Li; Maozhou He; Yangtao Wu; Yongchao Li; Rui Zhu; Hai Yu; Qiyang Hong; Jie Jiang; Zizhen Li; Shuxuan Li; et al. (Nature Communications, 2017)
Coxsackievirus A6 (CVA6) causes hand, foot and mouth disease in children. Here the authors present the CVA6 procapsid and A-particle cryo-EM structures and identify an immune-dominant neutralizing epitope, which can be exploited for vaccine development.